Reducing Energy Penalty in Wastewater Treatment: Fe-Cu-Modified MWCNT Electrodes for Low-Voltage Electrofiltration of OMC - Lu Yu; Jun Zeng; Xiu Fan; Fengxiang Li; Tao Hua (Energies)
Pseudo-persistent organic pollutants, such as pharmaceuticals, personal care products (PPCPs), and organic dyes, are a major issue in current environmental engineering. Considering the limitations of traditional wastewater treatment plant methods and degradation technologies for organic pollutants, the search for new technologies more suitable for treating these new types of pollutants has become a research hotspot in recent years. Membrane filtration, adsorption, advanced oxidation, and electrochemical advanced oxidation technologies can effectively treat new organic pollutants. The electro-advanced oxidation process based on sulfate radicals is renowned for its non-selectivity, high efficiency, and environmental friendliness, and it can improve the dewatering performance of sludge after wastewater treatment. Therefore, in this study, octyl methoxycinnamate (OMC) was selected as the target pollutant. A new type of electrochemical filtration device based on the advanced oxidation process of sulfate radicals was designed, and a new type of modified carbon nanotube material electrode was synthesized to enhance its degradation effect. In a mixed system of water and acetonitrile, the efficiency of the electrochemical filtration device loaded with the modified electrode for degrading OMC is 1.54 times that at room temperature. The experimental results confirmed the superiority and application prospects of the self-designed treatment scheme for organic pollutants, providing experience and a reference for the future treatment of PPCP pollution.